2013
DOI: 10.1039/c3cc44578j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of a BiCuSeO system via band gap tuning

Abstract: Upon 20% Te substitution, the band gap decreases from 0.8 eV to 0.65 eV. Rising temperature promotes minority carrier jumps across the band gap, thereby improving electrical conductivity. With low thermal conductivity and large Seebeck coefficients, a remarkable ZT of 0.71 at 873 K is achieved for BiCuSe0.94Te0.06O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 19 publications
6
48
0
Order By: Relevance
“…The zT of BiCuSeO has been increased to~1.5 through various approaches (see Fig. 17 b-f) including element doping (Mg, Sr, Ca, Ba, Pb at Bi site, Cu vacancies) [51,53,59,165,166], alloying (S, Te) [167], modulation doping [57] and texture treatment [56]. The findings and design methodology of this material are of valuable significance to investigation on similar layered compounds such as SnSe.…”
Section: Other High-performance Cu-based Chalcogenidesmentioning
confidence: 94%
“…The zT of BiCuSeO has been increased to~1.5 through various approaches (see Fig. 17 b-f) including element doping (Mg, Sr, Ca, Ba, Pb at Bi site, Cu vacancies) [51,53,59,165,166], alloying (S, Te) [167], modulation doping [57] and texture treatment [56]. The findings and design methodology of this material are of valuable significance to investigation on similar layered compounds such as SnSe.…”
Section: Other High-performance Cu-based Chalcogenidesmentioning
confidence: 94%
“…Recently, the related oxychalcogenides [BiO][CuQ] (Q¼ S, Se, Te), which consist of [Bi 2 O 2 ] 2 þ layers alternating with [Cu 2 Q 2 ] 2 À layers [17], have been identified as promising p-type thermoelectric materials. In this system, it has been shown that the substitution of Se by Te leads to an increase in electrical conductivity [18,19], together with a reduction in the thermal conductivity ( $ 0.97 W m À 1 K À 1 for BiOCuSe [20] and 0.68 W m À 1 K À 1 for BiOCuTe [21] at 373 K). Consequently, the figure of merit of the oxytelluride (ZT¼ 0.42 at 373 K) is significantly higher than that of the oxyselenide (ZT ¼0.15 at 373 K) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods have been employed to tune the electrical and thermal properties, including doping to optimize charge carrier concentration3334353637 and tune the transport properties of carriers38, introducing Cu deficiencies39 and band gap tuning to enhance electrical conductivity40, and texturing to improve the mobility of carriers41. The crystal structure of BiCuSeO belongs to the ZrSiCuAs-type structure with the tetragonal P 4/ nmm space group that constitutes the alternately stacked (Bi 2 O 2 ) 2+ insulating layers and (Cu 2 Se 2 ) 2− conductive layers along the c -axis of the tetragonal cell, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%